Employee Satisfaction and Electronic Workflow in Healthcare Organizations - Qandeel, Mahmoud Salameh (Marketing & Menedzsment, 2025)
THE AIM OF THE PAPER This study conducts a descriptive analysis to evaluate the perceived electronic workflow and satisfaction of staff members in a healthcare setting; furthermore, it analyzes whether the staff members are satisfied with the five facets of this electronic system. METHODOLOGY Following the evaluation, a questionnaire was piloted with a small group of healthcare employees. The study subsequently studied the five aspects of “electronic workflow”–electronic “work”, “transfer”, “audit and control”, „delay or postponement”, and „save and store” – in more detail by first conducting a descrip tive analysis and then running a stepwise regression analysis. MOST IMPORTANT RESULTS Descriptively, employees demonstrated a positive perception of the electronic workflow, with consistently high estimations across various aspects, which reflects the system’s effectiveness in facilitating work processes and meeting staff expectations. In the regression, electronic (work, “delay or postponement”, “audit and control”, and “save and store”) were substantial predictors of employee satisfaction, but electronic transfer was not. RECOMMENDATIONS The study emphasized the significance of electronic systems in facilitating work, enhancing staff satisfaction, and improving receiving services. Notably, organizations must continuously optimize electronic processes by employing recent technologies to embrace developments.